Doing Critical Language Teaching through Tasks: Insights from the Brazilian Context - Priscila Fabiane Farias; Leonardo da Silva (MDPI AG, 2021)
Although Brazilian governmental documents have conceived language teaching from a critical perspective, the recent scenario points to a backlash towards critical perspectives on teaching, which have been socially perceived as indoctrination. Since we understand critical pedagogy in additional language classrooms as a necessary emancipatory perspective, this article aims at discussing possibilities for promoting critical language development. More specifically, it draws on two doctoral studies in which teacher-researchers implemented critical task cycles that aimed at promoting critical language development by fostering elementary and high school students' reflections on gender issues. In both studies, tasks were developed to promote learners' communicative and critical development following task-based principles. The comparison of the results, derived from the analysis of learners' interactions during implementation, responses to questionnaires and interviews, and of the teacher-researchers' self-report diaries, revealed not only the feasibility of teaching critically through tasks, but also the positive role of: (1) A critical needs-analysis in designing and implementing critical tasks; (2) the use of critical dialogue for fostering knowledge co-construction; (3) the development of final projects to challenge common-sense discourses. These findings indicate, thus, relevant principles for teaching critically through tasks, emphasizing possibilities and challenges for promoting social transformation.